2019
DOI: 10.1016/j.envres.2019.02.031
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of bone lead measured via portable x-ray fluorescence across and within bones

Abstract: Background: Bone lead measured via x-ray fluorescence (XRF) has been used for decades in health studies. A portable XRF device for bone lead measurement is gaining in popularity for its ease of use and shorter measurement times. Previous XRF devices have measured different bone types in order to sample both cortical and trabecular bone, in which lead has different half residence times. Objective: The portable XRF uses lower energy to measure bone lead than previous devices, and, thus, only measures the surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Furthermore, given that lead deposits widely in soft tissue and skeleton (11), such modest elevations may underestimate the biologic consequences of repeated exposures over time. Total body lead accumulation, as can be measured with lead x-ray fluorescence (12)(13)(14), has been more closely associated with adverse health outcomes, some of which may develop many years after exposure (15)(16)(17)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, given that lead deposits widely in soft tissue and skeleton (11), such modest elevations may underestimate the biologic consequences of repeated exposures over time. Total body lead accumulation, as can be measured with lead x-ray fluorescence (12)(13)(14), has been more closely associated with adverse health outcomes, some of which may develop many years after exposure (15)(16)(17)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…In epidemiological health studies, it has been shown that excluding those values below a limit of detection can reduce efficiency and result in biased effect estimates for relations between the exposure and health outcomes. [ 36 38 ] Because Mn is primarily an occupational exposure for welders, we focused only on the welders for our Mn analyses. Nail salon workers had a higher exposure to Hg, although likely not occupational, so we restricted to nail salon workers in the Hg analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Each sample was analyzed with a 3-minute measurement. Then the data were analyzed using the standard procedure of previous studies (Specht et al, 2019;Specht et al, 2014;Zhang et al, 2021). Brie y, the Lβ peak (12.6 keV) was used for estimating Pb concentrations using a Gaussian function.…”
Section: Blood Lead Measurementmentioning
confidence: 99%